Use of Bakri balloon tamponade (BBT) for conservative management of postpartum haemorrhage: a tertiary referral centre case series. (2nd January 2018) - Mathur, Manisha; Ng, Qiu Ju; Tagore, Shephali
Abstract: The aim of this study was to investigate the efficacy of the Bakri balloon in the management of PPH. This was a retrospective review of 49 patients, who had Bakri balloon inserted for PPH in KK Hospital between April 2013 and December 2015. The main outcome measure was achievement of haemostasis by Bakri balloon tamponade (BBT). Our success rate was 81.6%. Out of the nine failures (18.0%), five (55.6%) had subtotal hysterectomies and four (44.4%) had total hysterectomies. The causes of PPH in these nine women were unsuspected or foci of placenta accreta (55.6%), uterine atony (33.3%) and retained products of conception (11.1%). Our study suggests that BBT is more likely to fail when bleeding is secondary to undiagnosed focal placenta accreta ( p  = .011) and when the estimated blood loss is more than 1.5 litres ( p  < .001). Our study adds to the growing body of evidence that BBT is not only effective for management of PPH in haemodynamically stable patients and in cases secondary to uterine atony and placenta praevia, but also in a small number of undiagnosed focal placenta accreta. Impact statement: There is limited evidence regarding efficacy of BBT for PPH. Our study supports the use of BBT for PPH due to uterine atony and placenta praevia and in a small number of undiagnosed placenta accreta.